PENERAPAN MEDIA PEMBELAJARAN PAPAN PINTAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA MATERI MENGENAL HURUF SISWA KELAS I SD NEGERI 5 GU KABUPATEN BUTON TENGAH - Rezki; Syekh Adiwijaya Latief; Amal Akbar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Smart Board learning media and its effectiveness in improving early reading skills among first-grade students at SD Negeri 5 Gu, Central Buton Regency. This classroom action research was conducted in two cycles consisting of planning, action, observation, and reflection. The participants were 15 students, and the data were collected through observations and oral tests, then analyzed descriptively using percentage techniques. The results showed that the Smart Board media increased students’ learning activity and early reading ability. Mastery learning improved from 40% in Cycle I to 86.66% in Cycle II, surpassing the classical mastery criterion of 80%. Students also demonstrated higher motivation, participation, and accuracy in recognizing letters and reading simple words. Thus, the Smart Board effectively enhances early reading skills in first-grade students